Uma introdução à álgebra geométrica e aplicações em detecção de objetos em imagens - Vinícius Riter de Faria (2018)
In this work we bring a brief study on Geometric Algebra, where we will address only basic definitions and results, followed by some concepts that lead us to the algebraic representation of geometric objects. We introduce the LIGA library, which was built with the purpose of making possible the computation using concepts of Geometric Algebra in the Julia language. Finally, to illustrate the use of the LIGA library in the detection of objects in images, we present an algorithm for circle detection inspired by the Hough Transform